Creating Space and Pathways for Elder Knowledge Transfer in University Settings - Colleen Kawalilak (Adult Education Research Conference, 2007)
This preliminary exploration of the literature informs a subsequent study that will focus on the richness of Elder faculty knowledge and how creating spaces for Elder knowledge sharing and knowledge transfer will significantly contribute to the overall quality of faculty life and learning for Other less senior faculty members.